Students’ Perception of The Implementation of Blended Learning at Junior High School - Dyah Djuwita; Rahmat Nasrullah; Faridawati Faridawati (FKIP Universitas Muhammadiyah Kendari, 2022)
This study aims to determine how students perceive the use of WhatsApp to support blended learning at SMPN 1 Motui. This study aims to determine how students perceive the use of WhatsApp to support blended learning at SMPN 1 Motui. The design in this research is descriptive qualitative using a questionnaire and interview instruments. In collecting data through questionnaires the researcher used a questionnaire sheet with two yes/no scales which were distributed to all students in one class and interviewed 6 students. The subjects in this study were 23 students of class IX. The results of the questionnaire showed that students gave a positive perception of the use of WhatsApp as a learning medium. They feel comfortable learning by using WhatsApp media in the learning process. The results of the interview revealed that teachers use WhatsApp to send learning materials in the form of document files, while students send assignments in the form of files, text and picture and students fill out the attendance list. However, there are also challenges in using WhatsApp including unstable network connections, limited internet quota and not having a mobile phone. This study also revealed that using WhatsApp can provide convenience for students including: 1) students can learn remotely anywhere and anytime, 2) can convey/receive information on learning materials, 3) easily send assignments, 4) can easily interact with teachers or classmates, 5) can increase positive attitudes and student learning outcomes in class.